Special exercises for the execution of the technique of bouncing in men´s Basketball - Oleneide Belicer-Gutiérrez; Olimpo Traba-Guibert (Universidad de Guantánamo, 2013)
In the present paper, a study on the weaknesses in the teaching-learning process in the execution of technical rebound in the men's basketball team, 9 to 10 years category, was conducted in the West Sports Complex in Guantanamo to coaches who are engaged in this activity, which have adversely affected the ability of athletes of this team to execute this technique. The above expressed is reflected in the failure to obtain a better result in the competitions of this sports in Children´s Provincial Championships. For the development of this paper some research methods were used, in the empirical and theoretical levels, which are: the observation, judgment of experts, the historical and logical analysis and synthesis, and as investigative techniques interview and survey, also consultations within the Information Center of the Province of bibliographical and statistical materials. The proposal was to develop special exercises in order to improve the teaching-learning process in the execution of the rebound technique in those athletes. The proposal was evaluated by a group of specialists in the field, which issued favorable opinions on the feasibility of it. The result of this research shows that it is necessary to work in depth with technical specialists and coaches to incorporate special exercises to the training programs which are designed to improve the technical rebound in basketball athletes.